Self-assembled organic–inorganic magnetic hybrid adsorbent ferrite based on cyclodextrin nanoparticles - Denadai, Ângelo M. L.; De Sousa, Frederico B.; Passos, Joel J.; Guatimosim, Fernando C.; Barbosa, Kirla D.; Burgos, Ana E.; de Oliveira, Fernando Castro; da Silva, Jeann C.; Neves, Bernardo R. A.; Mohallem, Nelcy D. S.; Sinisterra, Rubén D. (Beilstein Journal of Organic Chemistry, 2012)
Organic–inorganic magnetic hybrid materials (MHMs) combine a nonmagnetic and a magnetic component by means of electrostatic interactions or covalent bonds, and notable features can be achieved. Herein, we describe an application of a self-assembled material based on ferrite associated with β-cyclodextrin (Fe-Ni/Zn/βCD) at the nanoscale level. This MHM and pure ferrite (Fe-Ni/Zn) were used as an adsorbent system for Cr3+ and Cr2O72− ions in aqueous solutions. Prior to the adsorption studies, both ferrites were characterized in order to determine the particle size distribution, morphology and available binding sites on the surface of the materials. Microscopy analysis demonstrated that both ferrites present two different size domains, at the micro- and nanoscale level, with the latter being able to self-assemble into larger particles. Fe-Ni/Zn/βCD presented smaller particles and a more homogeneous particle size distribution. Higher porosity for this MHM compared to Fe-Ni/Zn was observed by Brunauer–Emmett–Teller isotherms and positron-annihilation-lifetime spectroscopy. Based on the pKa values, potentiometric titrations demonstrated the presence of βCD in the inorganic matrix, indicating that the lamellar structures verified by transmission electronic microscopy can be associated with βCD assembled structures. Colloidal stability was inferred as a function of time at different pH values, indicating the sedimentation rate as a function of pH. Zeta potential measurements identified an amphoteric behavior for the Fe-Ni/Zn/βCD, suggesting its better capability to remove ions (cations and anions) from aqueous solutions compared to that of Fe-Ni/Zn.
Keywords: assembled particles; colloids; cyclodextrin; ferrite; hybrid materials